The Effect of Communicative Language Teaching ”Role Play” On The Students Speaking Competency Of Grade X In SMA N 1 Kubu in Academic Year 2013/2014 - ., I Kadek Suarsana; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Ini adalah penelitian eksperimen, dimana bertujuan untuk mengetahui apakah ada perbedaan yang signifikan pada berbicara siswa yang diajar dengan tehnik Role Play dan tehnik konvensional di siswa kelas 10. Cluster Random Sampling adalah tehnik pengambilan sampel yang digunakan dalam studi ini, dimana dua kelas dipilih secara acak sebagai sampel dalam penelitian ini. Hasil dari descriptive statistics menunjukan hasil rerata nilai kelompok eksperimen 73.96 dan kelompok control 64.58. Lebih lanjut, analisis secara statistik inferensial menunjukan nilai t observed (to) adalah 3.198. Nilai tersebut lebih besar dari nilai t critical value (tcv) yaitu 1.67 (α = .05). Berdasarkan hasil penelitian tersebut, bisa di simpulkan bahwa ada perbedaan yang signifikan pada hasil berbicara siswa yang diajarkan dengan menggunakan tehnik Role Play dan siswa yang diajarkan dengan menggunakan tehnik konvensional. Kata Kunci : Keywords: Role Play, Conventional, Speaking Achievement This research was an experimental research, which was aimed at investigating whether there was a significant difference in students' speaking achievement taught by using Role Play Technique and Conventional Technique in tenth grade students. Cluster random sampling was used as sampling technique in this study, in which two classes were selected randomly as the samples of the study. The result of descriptive statistics shows that the mean score of experimental group was 73.96 while the control group was 64.58. Furthermore, from the analysis by using inferential statistic, it was found that the value of t observed (to) was 3.198. It was higher than t critical value (tcv) which was 1.67 (α = .05). Based on the data, it can be concluded that there is significant difference in speaking achievement of the students who are taught through Role Play Technique and the students who are taught by using conventional technique. keyword : Keywords: Role Play, Conventional, Speaking Achievement